1980
DOI: 10.1115/1.3240637
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Shedding From Two Circular Cylinders in Staggered Arrangement

Abstract: The frequency of vortex shedding from two circular cylinders of the same diameter in staggered arrangement is experimentally investigated at a Reynolds number of 1.58 × 104. This Reynolds number is within the range where the flow around a circular cylinder is relatively insensitive to Reynolds number changes. The results are summarized in several figures from which one can obtain the Strouhal number of vortex shedding for all arrangements within distances between their centers less than 5 diameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 0 publications
5
39
2
Order By: Relevance
“…The observations imply less quasi-periodic vortex shedding in Mode S-Ib than in Mode S-Ia, consistent with previous reports. Kiya et al (1980) observed weak vortex shedding from two staggered cylinders at P * 6 2.5 and α < 20 • . See region 2 in their figure 9.…”
Section: Mode S-ibmentioning
confidence: 85%
See 4 more Smart Citations
“…The observations imply less quasi-periodic vortex shedding in Mode S-Ib than in Mode S-Ia, consistent with previous reports. Kiya et al (1980) observed weak vortex shedding from two staggered cylinders at P * 6 2.5 and α < 20 • . See region 2 in their figure 9.…”
Section: Mode S-ibmentioning
confidence: 85%
“…A thin laser sheet, which was generated by laser beam sweeping, vertically illuminated the flow field at the mid-plane of the working section. The laser beam was produced by a Spectra-Physics Stabilite 2017 argon ion laser source with a maximum power output of 4 W. A digital video camera recorder (Sony Kiya et al (1980) at Re = 15 800; ᭢, Sumner et al (2000) at Re = 1350; ᭹, Alam & Sakamoto (2005) at Re = 55 000; ᭜ Sumner et al (2005) at Re = 50 000 are included for comparison. ᮀ, present data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations